Wiring olfaction: the cellular and molecular mechanisms that guide the development of synaptic connections from the nose to the cortex - De Castro, Fernando (Frontiers in Neuroscience, 2009)
Within the central nervous system, the olfactory system fascinates by its developmental and physiological particularities, and is one of the most studied models to understand the mechanisms underlying the guidance of growing axons to their appropriate targets. A constellation of contact-mediated (laminins, CAMs, ephrins, etc.) and secreted mechanisms (semaphorins, slits, growth factors, etc.) are known to play different roles in the establishment of synaptic interactions between the olfactory epithelium, olfactory bulb (OB) and olfactory cortex. Specific mechanisms of this system (including the amazing family of about 1000 different olfactory receptors) have been also proposed. In the last years, different reviews have focused in partial sights, specially in the mechanisms involved in the formation of the olfactory nerve, but a detailed review of the mechanisms implicated in the development of the connections among the different olfactory structures (olfactory epithelium, OB, olfactory cortex) remains to be written. In the present work, we afford this systematic review: the different cellular and molecular mechanisms which rule the formation of the olfactory nerve, the lateral olfactory tract and the intracortical connections, as well as the few data available regarding the accessory olfactory system. These mechanisms are compared, and the implications of the differences and similarities discussed in this fundamental scenario of ontogeny.